JENIS-JENIS HAMA DAN SERANGANNYA PADA TANAMAN NILAM - Michellia Darwis (Pusat Penelitian dan Pengembangan Perkebunan, 2005)
Pests Of Patchouli Plant And Their DamageGenerally, patchouli is still cultivated traditionally in Indonesia. Improved technology such as pest and disease control methods, is needed. Observation of pests on patchuoli was carried out at Sukamulya experimental garden from Agustus 2004 to January 2005. Further research was carried out at the laboratory and greenhouse of the Indonesian Spice and Medicinal Crops Research Institute to examine the damage of the patchouli plant due to the main insect attack. The experiment was arranged in a randomized block design, with 6 treatments and 4 replications. The experiment used one month-old patchouly seedlings of Sidikalang variety and the main insect (third instar grub) The white grub was invested on pathouli seedling. Each plant was invested with 0, 1, 2, 3, 4, 5, grubs as treatments. The results showed that grasshopper (Valanga sp), aphids (Myzus persicae), termite (Coptotermes sp), snail (Achatina sp) and white grub (Exopholis hypoleuca) attack the patchouly plant with low up to high damages. It was observed that the grub is a dominant pest which attacked 1.800 out of 15.000 patchouli plants at Sukamulya experimental garden. Treatments grubs on patchouli seedlings at one, two, three, four and five grubs/polybag caused death on the seedlings at 14, 13, 10, 7 and 7 days after investation, repectively. While the control seedlings were still alive until the end of the experiment.